Retheorising distributed leadership through epistemic injustice - Tian, Meng; Nutbrown, Graham (Educational management, administration & leadership, 2023)
Existing distributed leadership (DL) theories tend to focus on distributing financial, material and human resources in order to enhance school performance. However, their impact appears controversial. Critical scholars assert that using DL to promote trust and democracy can be a self-fulfilling prophecy orchestrated by few formal leaders. When being misused as a managerial tool, DL can reinforce epistemic injustice in school. In this conceptual paper, we retheorise DL through the lens of epistemic injustice. Drawing on the concepts of testimonial, hermeneutical and systemic injustice, we analyse how DL practices potentially marginalise, silence, and reject individuals as knowledge contributors due to their deflated credibility, the lack of concepts or language, and systemic discrimination. To build epistemic justice and reciprocity into DL, we propose three moves: building trust and self-trust; re-distributing epistemic resources; and reconfiguring relational justice. This paper makes a theoretical contribution by explicating why and how epistemic injustice is done to disadvantaged individuals in DL. It also serves as the theoretical foundation for future empirical investigations.